2016
DOI: 10.3390/ijerph13050516
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Associations between Body Mass Index and Hyperlipidemia among Adults in Northeastern China

Abstract: Background: There is evidence that body mass index (BMI) is closely related to hyperlipidemia. This study aimed to estimate the cross-sectional relationship between Body Mass Index (BMI) and hyperlipidemia. Methods: We recruited 21,435 subjects (aged 18–79 years and residing in Jilin province, China) using the multistage stratified cluster random sampling method. Subjects were interviewed with a standardized questionnaire and physically examined. We analyzed the cross-sectional relationship between BMI and hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 27 publications
3
36
2
2
Order By: Relevance
“…Current smoking (≥1 cigarette per day) was defined by subjects' self-report. Body mass index (BMI) was calculated as weight (kg) divided by height squared (m 2 ), and overweight or obesity was defined as BMI ≥26 kg/m 2 [19]. Physical inactivity was defined as physical exercise < 3 times a week for < 30 min each time, and this included industrial and agricultural labour [20].…”
Section: Definitions Of Stroke and Evaluation Of Risk Factorsmentioning
confidence: 99%
“…Current smoking (≥1 cigarette per day) was defined by subjects' self-report. Body mass index (BMI) was calculated as weight (kg) divided by height squared (m 2 ), and overweight or obesity was defined as BMI ≥26 kg/m 2 [19]. Physical inactivity was defined as physical exercise < 3 times a week for < 30 min each time, and this included industrial and agricultural labour [20].…”
Section: Definitions Of Stroke and Evaluation Of Risk Factorsmentioning
confidence: 99%
“…Moreover, a case-control study on 164 patients with 30 -64 years of age showed a significantly decreased level of serum lipids in people exposed to smoke, when compared to non- (35). Similarly, a Chinese study showed a significant nonlinear association between BMI and raised risk of hyperlipidemia, with a significantly increased trend of odds ratio following 1 kg/m2 increase in BMI (8).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the prevalence of hyperlipidemia in China has been reported to be 51.09%. There was also a frequency of 8.68% in rural and 5.74% in urban areas of India (8,20).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The general mental health status of the participants was evaluated, using the 12-item general health questionnaire (GHQ-12). For further information, the methods are fully described in our articles (6,7). SPSS version 19.0 was used for statistical analysis.…”
mentioning
confidence: 99%